2- A Drum’s Trans-Atlantic Journey from Africa to the Americas and Back after the end of Slavery: Annobonese and Fernandino musical cultures. - Aranzadi, Isabela de (African Sociological Review, 2010)
Musical instruments are an intrinsic part of culture accompanying people as an essential fac- tor in shaping the identity preserved through memory. In equatorial guinea there are some ethnic and social groups: fang, Bubi, ndowe, etc. It is in relation to the Annobonese and the fernandinos musical culture, that the concept of “Return trip to Africa” becomes meaning- ful. This paper discusses this focusing on instruments such as cumbé, kunkí, and dances such as cumbé or bonkó, which constitute an African legacy that has returned and has become a part of equatorial guinea’s musical culture. The paper’s main point is that the identity given by the African elements has remained active until today.